CHARAKTER PRAWNY ODPOWIEDZIALNOŚCI ZAWODOWEJ W BUDOWNICTWIE - Majchrzak, Bartosz (Zeszyty Prawnicze, 2016)
THE LEGAL NATURE OF PROFESSIONAL LIABILITY IN THE CONSTRUCTION INDUSTRY Summary The article concerns the legal nature of professional liability in the construction industry (Articles 95-101 of Ustawa z dnia 7 lipca 1994 r. – Prawo budowlane: the Polish Construction Act of July 7, 1994; Dz.U. 2013, Item. 1409; with later amendments; hereinafter P.b.). This issue requires an analysis of the relevant norms of P.b. in the context of the typical characteristics of administrative and disciplinary liability. It can be concluded that the professional liability of persons performing independent technical duties in the construction industry has a specific character, combining elements of administrative law with the solutions adopted for disciplinary penalties. The function of this liability and its essential procedural regulations, which are subject to the Polish Administrative Procedure Code (Kodeks postępowania administracyjnego) suggest its nature is administrative. However, a number of specific regulations have been drawn from the model applicable in disciplinary liability (including the deciding authority, the initiator of the proceedings, the prosecutor’s function, moderation of penalties, the catalogue of penalties, the institution of limitation of proceedings, entry of records in the register of sentenced persons and its erasure). As a result, we can formulate an objection of incoherent regulation.